Ontologie-basierte Definition von Anforderungen an Validierungswerkzeuge in der Fahrzeugtechnik - El-Haji, Mohanad (Karlsruher Schriftenreihe Fahrzeugsystemtechnik / Institut für Fahrzeugsystemtechnik, 2016)
Validation and verification are central activities of product engineering. The aim of these activities is to predict and evaluate the future system behaviour of the product in development. This is achieved by conducting tests and interpreting the generated measurement data. This work introduces an ontology-based method for increasing the efficiency and effectively of innovative automotive development projects, especially in cases where an organisational knowledge base does not exist yet.